OPENING NEW DOORS: SYNTHESIS OF ISLAMIC SCIENCE AND MODERN SCIENCE IN THE PHILOSOPHICAL BASIS OF THIS CENTURY - Eka Safitri, Ulfi Nabila; Ambarwati, Hasna; Yulianasari, Cantika; Nurul Fatikhah, Silmia Rasyida; Muthohar, Ahmad (Sanjiwani: Jurnal Filsafat, 2024)
There is a gap between Islamic science and modern science that needs to be addressed. This study seeks to bridge this gap with the philosophical foundations of this century and identify points of contact and differences between Islamic scientific paradigms and modern science. Through this approach, we hope to find a way to strengthen and integrate the two so as to produce new insights that are holistic and comprehensive by considering the philosophical foundations of this era. This research uses research methods with library research After the data and facts are obtained, they will be processed using the method used in writing this article, namely the philosophical-historical method.